Analysis of the evolution of foreign direct investment in the coal mining sector in Colombia from 2002 to 2013 - Plazas Díaz, Fabián Alfredo (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article studies the evolution of foreign direct investment (FDI) in themining and quarrying sector and the extraction of coal, lignite and peat inColombia in the period 2004-2013 using statistics from the central bank ofColombia (Banco de la República) and from the Colombian Mining InformationSystem. An outlook of the coal mining industry in Colombia andthe evolution of IED are presented for the described period. We concludethat coal mining in Colombia has enormous potential that favored the entryof foreign capital during the period, but ended up being an indicator ofprimarization of IED in the country.